Efficacy and factors influencing outcomes of customized music therapy combined with a follow-up system in chronic tinnitus patients - Yuehong Liu; Siyi Yang; Yulu Wang; Jiahua Hu; Hongbo Xie; Tianyi Ni; Zhao Han (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Backgrounds Tinnitus is a meaningless sound signal perceived by the patients in the absence of auditory stimuli. Due to the complex etiology and unclear mechanism, specific therapies for tinnitus are still in the exploratory stage. In recent years, personalized and customized music therapy has been proposed as an effective method for tinnitus treatment. The aim of this study was to explore the efficacy of customized therapy with a well-designed follow-up system in the treatment of tinnitus through a large sample one arm study and to identify the relevant factors affecting the treatment outcome. Methods The study investigated a total of 615 patients with unilateral or bilateral chronic tinnitus who received personalized and customized music therapy for 3 months. A complete follow-up system was designed by the professionals. Questionnaires of Tinnitus Handicap Inventory (THI), Hospital Anxiety and Depression Scale (HADS) and Visual Analogue Scale (VAS) were used to evaluate the therapeutic effects and relevant factors affecting the efficacy of therapy. Results The results showed a decreasing trend in THI and VAS scores after 3 months of therapy, with statistically significant differences between pre- and post-therapy time points (P < 0.001). All patients were divided into 5 groups according to THI scores, and the mean reduction score in catastrophic, severe, moderate, mild and slight group was 28, 19, 11, 5, 0 respectively. The proportion of tinnitus patients with anxiety was higher than that with depression (70.57% and 40.65%, respectively), and there were statistically significant differences between HADS-A/D scores pre- and post-therapy. Binary logistic regression showed that the baseline of THI, VAS scores, the duration of tinnitus and the state of anxiety prior to therapy were significant influencing factors of therapeutic efficacy. Conclusions The magnitude of reduction in THI scores after music therapy depended on the severity of the patients' tinnitus, the higher the initial THI scores, the greater the potential for improvement in tinnitus disorders. Music therapy also reduced the anxiety and depression levels of tinnitus patients. Therefore, personalized and customized music therapy with a comprehensive follow-up system may be an effective treatment option for chronic tinnitus patients. Graphical abstract